Mahasiswa Iain Kediri dan Dominasi Teknologi Herbert Marcuse - A Zahid; Rista Aulia Sholikhah; Siti Mariyam (Prodi Sosiologi Universitas Mataram, 2021)
Modern society has unknowingly been dominated by modern technology which makes humans passive and uncritical of social conditions, as well as receptive. That people no longer live with technology, but is controlled by technology, this rationality can be seen when cellphones do not have a connection to the internet, it can be said that they will be out of date because they cannot update the latest information. This becomes an interesting discussion because it is almost felt by students, especially students of IAIN Kediri. This research uses a critical study of Herbert Marcuse's technological rationality which leads to one-dimensional humans or commonly referred to as One Dimensional Man. Therefore, this study seeks to explain the phenomena that occur among students related to meeting the needs of data packages that can affect various aspects of their daily lives. The results of this study are the need for a data package for the students of IAIN Kediri as a primary need. This is because with the data package students are able to find out the latest information on matters related to lectures, on the other hand, with the student data package, smartphones are also dominated by various features in it.